Fungal Diversity in the Dry Forest and Salt Flat Ecosystems of Reserva Ecologica Arenillas, El Oro, Ecuador - Débora Masache; Fausto López; Ángel Benítez; Teddy Ochoa; Darío Cruz (Diversity, 2025)
Fungi are a diverse and essential group that play crucial ecological roles. However, they remain understudied in tropical countries like Ecuador in terms of their forest or protected areas, particularly across diverse ecosystem zones such as seasonal forests and salt flats. This study aimed to inventory fungal diversity in two specific zones: the dry forest (DF) and the salt flat (SF) within the Reserva Ecologica Arenillas (REAR), located in El Oro, Ecuador. The results recorded 162 specimens representing 47 species belonging to 34 genera, identified morphologically. Although statistically significant, the difference in species richness and abundance between the dry forest and the salt flat was minimal, with the dry forest showing slightly higher values. Nonetheless, certain species were prevalent in both ecosystems, such as Cerrena hydnoides, Pycnoporus sanguineus, Hexagonia tenuis, and Chondrostereum sp., alongside four species with resupinate habit, all of them growing on decayed wood. The Shannon and Simpson indices were calculated to assess alpha diversity, revealing higher diversity in the DF. To evaluate differences in community composition between habitats, non-metric multidimensional scaling (NMDS) and permutational analysis of variance (PERMANOVA) were applied, indicating greater species turnover and dominance of specific taxa in the DF compared to the SF. These findings highlight the importance of the fungal diversity found in the REAR while also pointing to the need for more exhaustive monitoring and comparative studies with other wild or protected areas to fully understand and conserve this biodiversity.